The Influence of Financial Literacy, Peers, and Self-Control on the Consumptive Behavior of Boarding House Students - Aisyah Amalia; Fauziyah Fauziyah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Among students, consumptive behavior is still a prominent phenomenon as access to digital services increases and the lifestyle of the younger generation changes. Boarding house students who have to manage their finances independently, far from family supervision, and vulnerable to social influences make this condition even more relevant. Factors that influence consumptive behavior have been widely studied in previous research, but studies discussing the role of financial literacy, peers, and self-control in the context of boarding house students are still limited. Therefore, this study aims to analyze the influence of these three factors on the consumptive behavior of students. A quantitative method was used in this study by distributing questionnaires to boarding house students, and then the data was analyzed. This study shows that financial literacy has a significant negative effect, while peers and self-control have a significant positive effect on consumptive behavior. This study found that self-control dynamics correlate positively with consumptive behavior, indicating the existence of situational self-control among boarding house students. The implications of this study emphasize the importance of financial knowledge integrated with community development and strengthening self-regulation to help students develop wiser consumptive behavior.